Powder diffraction and crystal structure prediction identify four new coumarin polymorphs. Issue 7 (15th May 2017) - Shtukenberg, Alexander G.; Zhu, Qiang; Carter, Damien J.; Vogt, Leslie; Hoja, Johannes; Schneider, Elia; Song, Hongxing; Pokroy, Boaz; Polishchuk, Iryna; Tkatchenko, Alexandre; Oganov, Artem R.; Rohl, Andrew L.; et al.
Abstract : Crystal structures of four new coumarin polymorphs were solved by crystal structure prediction method and their lattice and free energies were calculated by advanced techniques. Abstract : Coumarin, a simple, commodity chemical isolated from beans in 1820, has, to date, only yielded one solid state structure. Here, we report a rich polymorphism of coumarin grown from the melt. Four new metastable forms were identified and their crystal structures were solved using a combination of computational crystal structure prediction algorithms and X-ray powder diffraction. With five crystal structures, coumarin has become one of the few rigid molecules showing extensive polymorphism at ambient conditions. We demonstrate the crucial role of advanced electronic structure calculations including many-body dispersion effects for accurate ranking of the stability of coumarin polymorphs and the need to account for anharmonic vibrational contributions to their free energy. As such, coumarin is a model system for studying weak intermolecular interactions, crystallization mechanisms, and kinetic effects.